2014
DOI: 10.1017/s0033291714002153
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of cognitive decline in different types of dementia

Abstract: We show cognitive trajectories of different types of dementia. These estimations of natural disease course have important value for the design of clinical trials as neuropsychological measures are increasingly being used as outcome measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
89
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(98 citation statements)
references
References 33 publications
4
89
1
4
Order By: Relevance
“…Therefore it is sensible to include other cognitive domains (e.g. executive functions, attention, visuospatial functioning, language) in SCD assessments (34, 35). For example, recent work by Smart and collaborators demonstrated decrements in attention and decision-making, respectively, in persons with SCD as compared to healthy older controls (36, 37).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore it is sensible to include other cognitive domains (e.g. executive functions, attention, visuospatial functioning, language) in SCD assessments (34, 35). For example, recent work by Smart and collaborators demonstrated decrements in attention and decision-making, respectively, in persons with SCD as compared to healthy older controls (36, 37).…”
Section: Resultsmentioning
confidence: 99%
“…processing speed and executive impairment) are most commonly associated with late-life depression (28) and other forms of dementia (29). We found similar results with naMCI as the outcome suggesting that the sex difference in how depressive symptoms relate to risk of cognitive impairment also applies to non-memory domains and a risk of dementia.…”
Section: Resultsmentioning
confidence: 99%
“…By contrast, Wilson et al, using data from a longitudinal cohort study of 823 older adults, reported that loneliness was linked to a more rapid decline in semantic memory rather than episodic memory. On the other hand, the focus of most studies on single cognitive screening tests or aggregated results across diverse cognitive tasks might limit our potential to explore trajectories of different cognitive profiles . Markers of fluid abilities (eg, episodic memory) that are known to decline over the lifespan and to be impaired at the earlier stages of neurocognitive disorders might be more sensitive to the effects of loneliness and social isolation than those of crystallized abilities (eg, verbal fluency).…”
Section: Introductionmentioning
confidence: 99%